Juridical Overview on the Inconsistency of Prohibition to be the Member of Political Parties for the Members of Public Institutions - Fajar Prima Julian; Ratna Herawati (LAW REFORM, 2021)
The creation of a justice in the life of the nation and state must be supported by regulations that do not conflict with other regulations. The prohibition to join a political party for administrators of public institutions   is in conflict with higher regulations. The article is considered contrary to the principle of "Equality before the Law" when viewed from the aspect of equal concern put forward by Ronald Dworkin. The purpose of this research was to analyze the inconsistency of the prohibition article for members of public institutions   to join political parties and to explain the legal implications for the public institutions when they do not comply with these regulations. The method used was normative juridical with descriptive analytical research specifications, and the type of the data were secondary data. The data analysis was conducted qualitatively. Political rights are part of the human rights owned by a person who should not be limited by discriminatory treatments. In fact, there are still restrictions on these political rights which are detrimental to a person from contributing to become the administrator of a public institution. The contents of conflicting articles cause the public institutions to have a crisis of law compliance, is actually a hierarchical harmony between laws and regulations in Indonesia.